Mecanismos moleculares envolvidos no transporte de glicose e água no epitélio alveolar de ratos diabéticos - Oliveira, Tales Lyra de (2014)
The hyperglycemia resulting of the diabetes can promote metabolic and functional changes in several organs and systems, including the lungs. An example is the high glucose concentration in the airway surface liquid (ASL) that increases the growth of microorganisms, making it a risk factor for respiratory infections. The cotransporter Na+/glucose/H2O SGLT1 has been detected in rat alveolar epithelium, but the glucose transporter, GLUT2, has not been described in this epitelium. Considering, this study aimed to evaluate the effect of diabetes and the treatment with isoproterenol and phlorizin on glucose and water flows in the rat alveolar epithelium. This study was approved by the Ethics Committee on Animal Use (CEUA), from Federal University of Alagoas (UFAL), protocol 40/2012. Were used Wistar rats (n=6 per group) Non-Diabetics and Diabetics treated with saline (NDs and Ds) treated with isoproterenol (NDi and Di) or phlorizin (NDf and Df). The diabetes was induced by alloxan (40 mg/kg, iv) 21 days before the study. On 22nd day after the induction, the animals were treated intranasally with saline (0.9%), isoproterenol (5 mg/kg) or phlorizin (10-3 M). After 2h, the animals were anesthetized with sodium thiopental (60 mg/kg, ip) and then, was collect the bronchoalveolar lavage (BAL) and the thoracic cage was dissected for remove the lung. The lung lobes were systematically removed and sectioned. Thus it was performed the procedures for histology (HE and PAS) and immunohistochemistry (SGLT1 and GLUT2) analyses of the respiratory epithelium and measurement of water volume, concentration of glucose and total proteins of ASL using the bronchoalveolar lavage. The BAL was used to quantify the glucose concentration in the ASL. The results were expressed as mean ± SEM and compared with ANOVA/Newman-Keuls test (p< 0.05). The diabetes and the treatment with phlorizin promoted an increase in mucus production in the lumen of bronchial epithelium, but none of the experimental groups showed an alteration in histological structure in this epithelium. The volume of water and ASL glucose concentration and total proteins was increased (p< 0.05) in diabetic animals. The treatment with isoproterenol promoted a reduction (p< 0.05) of 17% and 50% of the water volume and the glucose concentration of ASL, respectively, while the administration of phlorizin produced opposite effect compared with isoproterenol-treated rats. The isoproterenol also provided the SGLT1 translocation to the plasma membrane of pneumocytes in normoglycemic and diabetic animals. Furthermore, the GLUT2 was described for the first time, with low protein expression, in these cells. The inoculation of MRSA and Pseudomonas aeruginosa on BAL revealed that the proliferation of these colonies increased in diabetic animals and in the animals treated with phlorizin, however was reduced in animals treated with isoproterenol. Taken together, our results suggest that isoproterenol promotes the translocation of SGLT1 to the luminal membrane of pneumocytes, favoring the reduction of glucose concentration and the liquid volume of ASL in diabetic animals, reducing the risk of respiratory complications. In addition, we observed that blocking of SGLT1 in the luminal membrane of pneumocytes by phlorizin increases the glucose concentration and the volume of ASL, which indicates that the alveolar SGLT1 might be an important modulator of the volume and composition of ASL.